PENGARUH WHATSAPP BROADCAST TERHADAP PENINGKATAN PENJUALAN PRODUK UMKM DI SLEMAN MART - Endah Wening Budiningrum; Subandi Subandi; Luluk Priyanti; Khoiri Najib (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
The purpose of this study is to determine the effect of whatsapp broadcast on increasing sales of UMKM products at Sleman Mart by comparing sales data in 2020 with 2021, where in 2020 marketing uses continuous whatsapp broadcasts and in 2021 uses discontinuous whatsapp broadcasts. The research method used is descriptive quantitative with a comparative approach. The results of this study show that there are differences in sales of UMKM products at Sleman Mart during 2020 with 2021 where the average sales in 2020 are greater than in 2021. In other words, there is an effect of WhatsApp broadcast on increasing sales of UMKM products at Sleman Mart.